2004
DOI: 10.1002/ajmg.b.20166
|View full text |Cite
|
Sign up to set email alerts
|

Family‐based association study of schizophrenia with 444 markers and analysis of a new susceptibility locus mapped to 11q13.3

Abstract: Family-based linkage disequilibrium (LD) mapping has been suggested as a powerful and practical alternative to linkage analysis. We have performed a genome-wide LD survey of susceptibility loci for schizophrenia in a Japanese population. We first typed 119 schizophrenic pedigrees (357 individuals) using 444 microsatellite markers, and analyzed the data using the pedigree disequilibrium test. This analysis revealed 14 markers demonstrating significant transmission distortion. To corroborate these findings, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Cyclin D1 maps to a locus on 11q13.3 that has been linked to bipolar disorder 117 and schizophrenia. 118 Last but not least, cyclin D1 gene expression was reported to be altered in post-mortem brains of human alcoholics. 59 Our data also show that alcohol-preferring rats have lower baseline levels of FYN and IGF1R than alcohol-non-preferring rats in the NAC, and that these levels are decreased by the ICSA of alcohol in the VTA ( Table 3).…”
Section: Za Rodd Et Almentioning
confidence: 99%
“…Cyclin D1 maps to a locus on 11q13.3 that has been linked to bipolar disorder 117 and schizophrenia. 118 Last but not least, cyclin D1 gene expression was reported to be altered in post-mortem brains of human alcoholics. 59 Our data also show that alcohol-preferring rats have lower baseline levels of FYN and IGF1R than alcohol-non-preferring rats in the NAC, and that these levels are decreased by the ICSA of alcohol in the VTA ( Table 3).…”
Section: Za Rodd Et Almentioning
confidence: 99%
“…67 Moreover, an investigation of linkage disequilibrium using 444 microsatellite markers in a Japanese sample identified 11q13 as a potential liability locus for schizophrenia, adding further interest in this area. 68 Chromosomes 13 and 14 Several molecular studies have replicated linkage locations on the long arm of chromosome 13 10,36 and highlighted putative susceptibility genes in this area. 69,70 The D-amino acid oxidase activator (DAOA; formerly known as G72) gene is regarded as a very promising candidate to the genetic risk for the disorder.…”
Section: Chromosome 11mentioning
confidence: 99%
“…The NFKB3 located on chromosome 11q13 showed a suggestive linkage to schizophrenia in a family-based linkage disequilibrium analysis in a Japanese population [69].…”
Section: Immune-associated Genesmentioning
confidence: 96%
“…A GWAS study in Caucasian population showed significant association with schizophrenia were in a region of LD on chromosome 6p22.1, including several immunity related genes other than the RELA gene [69]. However, the biological significance of this gene in susceptibility for schizophrenia might not be large, because 22% of the patients with schizophrenia have homozygous of risk allele in SNP4, but 16% of the controls also are homozygous of risk allele in SNP4.…”
Section: Immune-associated Genesmentioning
confidence: 99%